1998
DOI: 10.1007/s004649900851
|View full text |Cite
|
Sign up to set email alerts
|

Cosmesis and body image after laparoscopic-assisted and open ileocolic resection for Crohn's disease

Abstract: Laparoscopic surgery was associated with better cosmesis than open surgery. Patients do not experience laparoscopic surgery any differently from open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
272
4
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(286 citation statements)
references
References 14 publications
6
272
4
4
Order By: Relevance
“…Recently, for cholecystectomy, double-blinded RCT evaluating QOL between singleport cholecystectomy and conventional laparoscopic cholecystectomy was firstly reported (10). Using previously validated cosmesis and body image scores, and short form 36 health survey questionnaire SF-36, this study reported the statistical advantage of cosmesis and body image, higher QOL regarding emotional wellbeing, physical pain, physical health and mental health after postoperative 1 year, and less postoperative pain in single port cholecystectomy (47)(48)(49). However, quality of life in SIDG compared to TLDG was not comprehensively evaluated until now.…”
Section: Outcome and Understandingmentioning
confidence: 96%
“…Recently, for cholecystectomy, double-blinded RCT evaluating QOL between singleport cholecystectomy and conventional laparoscopic cholecystectomy was firstly reported (10). Using previously validated cosmesis and body image scores, and short form 36 health survey questionnaire SF-36, this study reported the statistical advantage of cosmesis and body image, higher QOL regarding emotional wellbeing, physical pain, physical health and mental health after postoperative 1 year, and less postoperative pain in single port cholecystectomy (47)(48)(49). However, quality of life in SIDG compared to TLDG was not comprehensively evaluated until now.…”
Section: Outcome and Understandingmentioning
confidence: 96%
“…They used the SF-36, the GIQLI, and the Body Image Questionnaire (BIQ [28]). The laparoscopic group was significantly more often satisfied with the cosmetic result of the operation.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Ao comparar pacientes submetidos à ressecção íleocólica vídeo-assistida, com outros submetidos à via aberta, notamos que a via laparoscópica tem maior tempo operatório, menor de internação e superioridade cosmética 32,33,34 . Além disso, alguns autores ainda relatam uma menor morbidade nos pacientes submetidos à via laparoscópica 35 Um estudo prospectivo, randomizado e multicêntrico observou ain-…”
Section: Resultados Da Videocirurgia Na Doença De Crohnunclassified